ANALISIS DAN PERANCANGAN SISTEM INFORMASI POINT OF SALE BERBASIS WEB PADA CV. YANTI - Yodi, Ryanto; Susilo, Joko (Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
CV. Yanti is a company that provides daily necessities (groceries). Every sale of this company can record many sales transactions, from the number of these transactions the company does not have an information system that can manage data transaction which makes it difficult for the company to manage each sales transaction. This research is intended to facilitate the company in managing existing sales transactions in the CV. Yanti. The supporting theory used in completing the system design analysis on CV. Yanti, namely Information Systems, Waterfall, Point of Sales, and others. Based on the above problems, researchers analyzed the system, and collected data through literature studies, observations and direct interviews on the CV. Yanti, from these results, researchers can find the main problem and can propose problem solution. The research used is the design of information systems consisting of system architecture design, use case diagrams, activity diagrams, class diagrams, menu structure design, form design and user manuals, and for manufacturing systems using JavaScript and PostgreSQL databases. The results showed that the design of this Point of Sale information system can provide convenience in managing data related to sales transactions on the CV. Yanti and management of sales transaction data becomes easier and more efficient. Keywords: Point of Sales, Analysis and Design of Information System, JavaScript and PostgreSQL